Berberine Attenuates Cerebral Vasospasm After Experimental Subarachnoid Hemorrhage Via Modulating AMPK/Rho Pathway - KUMAŞ, MELTEM; Kadirhan, Ozge Altintas; KOÇYİĞİT, ABDÜRRAHİM; Kumas, Meltem; ASİL, TALIP; Karatas, Ersin; Mutlu, Hasan Serdar; KOÇYİĞİT, ABDÜRRAHİM; Asil, Talip (My University, 2020)
Purpose: Our goal is to clarify the effectiveness of berberine (BBR) on cerebral vasospasm induced by subarachnoid hemorrhage.